Isolation of Heterozygous Diploid Strain in Alternaria Alternate Fungus - Huda W. Hadi (Algerian Journal of Research and Technology (AJRT), 2021)
In this study, 31 spontaneous or UV-induced mutants were isolated. Some of the mutants were white (w) (melanin missing), others were nitrate auxotrophic (nit); others were sulphate auxotrophic (s), and others combined the colored and auxotrophy genotypes. In addition, two strains one of them black Chl10 strain, nitrate auxotrophic, has the genotype (nit10, w2 +, s2 +) and the white Sel2 strains up hate auxotrophic, has the genotype (nit10 +, w2s2)both were used in genetic analyses in this fungus. The heterozygous diploid strain was isolated after heterokaryon formation in Alternaria alternata fungus. However, using heterokaryon and heterozygous diploid genetic analyses showed for the first time in this fungus that the basic steps for para sexual analysis are available in this fungus. This makes it feasible to do further genetic studies in this imperfect species to elucidate the genetic control of melanin and other secondary metabolites (e.g. host-specific toxins) which are thought to be essential for pathogenicity.